Depression as comorbidity of rheumatoid arthritis - Baerwald, C.; Manger, Bernhard; Hueber, Axel (Zeitschrift für Rheumatologie, 2019)
Depressive disorders are among the most common comorbidities in patients not only with rheumatoid arthritis (RA) but also with other forms of inflammatory rheumatic diseases. The prevalence of adepressive disorder in RA is estimated to be between 9.5% and 41.5% depending on the study and with women being more affected. After adjusting for sex, age and other parameters the risk of depression in RA was significantly elevated with an odds ratio of 1.63 (95% CI, 1.43-1.87) compared to the general population. In RA the risk of developing adepressive disorder is highest in the first 5 years and depression is abetter predictor of work disability than disease activity and response to treatment. Depression in RA is associated with more pain, fatigue and impaired quality of life, whereby the association between depression and RA is bidirectional. Therefore, the risk to develop adepression is increased with impaired function as measured by the health assessment questionnaire (HAQ) and there is evidence that increased disease activity increases the risk for depression in RA. In addition, adepressive disorder also affects the subjective severity of patient-reported outcomes (PRO), such as tender joints and the global patient assessment with respect to disease activity and thus exhibiting adirect influence on the DAS28. Finally, it could be shown that depression unfavorably influences the response to therapy, the rate of remission is lower and the mortality is increased in RA patients. Taken together, this indicates that it is necessary to detect a depression in patients with RA as early as possible in order to initiate appropriate treatment of depression in such cases.
CRIS-Team WoS Importer:2019-04-16